Deterministic Quantum Key Distribution Using Gaussian-Modulated Squeezed States - 何广强 朱俊 曾贵华 (Communications in theoretical physics, 2011)
A continuous variable ping-pong scheme, which is utilized to generate deterministic private key, is proposed. The proposed scheme is implemented physically by using Ganssian-modulated squeezed states. The deterministic char- acteristic, i.e., no basis reconciliation between two parties, leads a nearly two-time efficiency comparing to the standard quantum key distribution schemes. Especially, the separate control mode does not need in the proposed scheme so that it is simpler and more available than previous ping-pong schemes. The attacker may be detected easily through the fidelity of the transmitted signal, and may not be successful in the beam splitter attack strategy.